2016
DOI: 10.3171/2015.8.jns151211
|View full text |Cite
|
Sign up to set email alerts
|

Utility of arterial spin labeling perfusion magnetic resonance imaging in prediction of angiographic vascularity of meningiomas

Abstract: OBJECTIVE Arterial spin labeling perfusion-weighted imaging (ASL-PWI) enables quantification of tissue perfusion without contrast media administration. The aim of this study was to explore whether cerebral blood flow (CBF) from ASL-PWI can reliably predict angiographic vascularity of meningiomas. METHODS Twenty-seven patients with intracranial meningiomas, who had undergone preoperative ASL-PWI and digital subtraction angiography prior to resection, were included. Angiographic vascularity was assessed using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…On the other hand, Noguchi et al have proposed that ASL-driven CBF may predict histopathologic vascular densities of brain tumors [16]. Recently, Yoo et al have demonstrated that ASL may predict the angiographic vascularity of meningiomas [22]. Thus, elevated intratumoral CBF in GBM compared to brain metastasis in our study may reflect the difference in vascular density, although the exact pathologic mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…On the other hand, Noguchi et al have proposed that ASL-driven CBF may predict histopathologic vascular densities of brain tumors [16]. Recently, Yoo et al have demonstrated that ASL may predict the angiographic vascularity of meningiomas [22]. Thus, elevated intratumoral CBF in GBM compared to brain metastasis in our study may reflect the difference in vascular density, although the exact pathologic mechanisms remain unclear.…”
Section: Discussionmentioning
confidence: 63%
“…Because it is very hard to designate a specific MR scanner for certain target patients before knowing their diagnosis in clinical practice, it may be reasonable to find a way to handle such inter-scanner variation. To minimize possible bias associated with different magnetic strengths, we analyzed the data with a normalized CBF [16, 2022]. The effect of different magnetic strengths to perfusion parameters was not significant, except for nCBF peritumoral in brain metastasis group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASL has also been used to perform meningioma grading and identify high grade aggressive forms [15]. Non selective ASL was used by Yoo et al to assess meningioma vascularity in comparison to DSA and found a high positive correlation between the two modalities [16]. Kikichi et al investigated the added values of ASL as an additional tool to detect recurrent meningioma and found an increased detection rate among non-specialists [17].…”
Section: Discussionmentioning
confidence: 99%
“…The utility of ASL perfusion imaging in the evaluation of the vascularity of brain tumors has been explored in several recent studies. [11][12][13][14] One prior study differentiated hemangioblastomas from metastases on the basis of quantitative blood flow measurements using ASL. 15 The authors reported that tumor blood flow was significantly higher in hemangioblastomas than in metastases.…”
mentioning
confidence: 99%